Predictors of Hypothyroidism after Thyroid Lobectomy - Thahab, Shafi Shadhar; Almomin, Ammar M. S.; Al-Zajaji, Qusay B.J.; Mansour, Abbas A. (Ibnosina Journal of Medicine and Biomedical Sciences, 2023)
Background The reported incidence of postlobectomy hypothyroidism is quite different among studies with an average of 22%. Many risk factors predict the development of hypothyroidism in patient undergoing thyroid lobectomy.Aim The aim of this study was to assess predictors of hypothyroidism after thyroid lobectomy.Methods A retrospective observational study was conducted at Faiha Specialized Diabetes, Endocrine, and Metabolism Center and Zain Alabdeen Teaching Hospital during a period of 9 months from January 2022 to October 2022. It included data of 80 patients collected from medical archives for individuals who had thyroid lobectomy regardless the cause. Information was collected regarding patient pre- and postlobectomy thyroid-stimulating hormone (TSH), thyroid peroxidase antibody, and antithyroglobulin antibody levels.Results In this study, 22.5% of patients developed hypothyroidism after lobectomy. Preoperative TSH level was substantially higher than average in patients who developed postlobectomy hypothyroidism than those who did not. The highest prevalence of postlobectomy hypothyroidism was seen significantly in patients with positive thyroid peroxidase autoimmunity and in those with positive thyroglobulin autoimmunity. Preoperative TSH level more than 2.61 mIU/L is a predictor for the risk of postlobectomy hypothyroidism.Conclusion Higher TSH level and thyroid autoimmunity predict higher risk of developing hypothyroidism after thyroid lobectomy.
Keywords: hypothyroidism; Iraq; lobectomy; predictors; thyroid